2000
DOI: 10.1111/j.1432-2277.2000.tb02043.x
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of 100 pregnancy outcomes in women treated systemically with tacrolimus

Abstract: The aim of this paper is to provide a summary of clinical findings regarding the safety of tacrolimus in pregnancy. From 1992 to 1998 data were collected on 100 pregnancies from 84 mothers who received tacrolimus systemically; 83 cases of solid organ transplantation, and 1 case of Behçet's disease. Maternal mean age at conception was 28 years and pregnancy outcome was live birth in 68%, spontaneous abortion in 12%, induced abortion in 12%, stillbirth/perinatal death in 3%, ongoing pregnancy in 2%, and lost to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
23
0
1

Year Published

2005
2005
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(26 citation statements)
references
References 2 publications
2
23
0
1
Order By: Relevance
“…Pregnancy in organ-transplanted women is associated with a high level of complications. Jain et al [45] reported on 27 pregnancies and found a surprisingly low incidence of maternal complications and, consistent with other studies [46,47], an incidence of preterm delivery and low birth weight similar to those described in other immunosuppressive agents. Due to the molecular size of calcineurin inhibitors, topical use results in poor systemic absorption [48] and is hence expected to be safe during pregnancy; however, due to the lack of human data the FDA has assigned it a pregnancy category C and topical corticosteroids are preferred.…”
Section: Calcineurin Inhibitorssupporting
confidence: 82%
“…Pregnancy in organ-transplanted women is associated with a high level of complications. Jain et al [45] reported on 27 pregnancies and found a surprisingly low incidence of maternal complications and, consistent with other studies [46,47], an incidence of preterm delivery and low birth weight similar to those described in other immunosuppressive agents. Due to the molecular size of calcineurin inhibitors, topical use results in poor systemic absorption [48] and is hence expected to be safe during pregnancy; however, due to the lack of human data the FDA has assigned it a pregnancy category C and topical corticosteroids are preferred.…”
Section: Calcineurin Inhibitorssupporting
confidence: 82%
“…Tacrolimus is considered to be a safe drug to use during pregnancy, without presenting any increase in malformation rate with its use. There are no digital defects related with this drug [17][18][19]. Another infant had two development defects: lingual thyroid and interatrial septum defect, and the third infant a pyeloureteral junction stenosis.…”
Section: Discussionmentioning
confidence: 99%
“…In general, in addition to prednisone, immunosuppressive medications that are considered permissible during pregnancy include azathioprine and cyclosporine. Use of tacrolimus is increasingly considered an effective alternative for patients who fail azathioprine: studies from the transplant literature suggest safety and tolerability in pregnancy [ 14 ] and pilot studies suggest effi cacy for lupus nephirits [ 15 ], including a case report of successful treatment of lupus nephritis with tacrolimus during lupus pregnancy [ 16 ].…”
Section: Medication Reviewmentioning
confidence: 98%